Identity Selection and the Social Construction of Birthdays - Pelham, Brett W.; DeHart, Tracy; Shimizu, Mitsuru; Hardin, Curtis D.; Han, H. Anna; Hippel, William von (Frontiers in Psychology, 2021)
We argue that rather than being a wholly random event, birthdays are sometimes selected by parents. We further argue that such effects have changed over time and are the result of important psychological processes. Long ago, U.S. American parents greatly overclaimed holidays as their children’s birthdays. These effects were larger for more important holidays, and they grew smaller as births moved to hospitals and became officially documented. These effects were exaggerated for ethnic groups that deeply valued specific holidays. Parents also overclaimed well-liked calendar days and avoided disliked calendar days as their children’s birthdays. However, after birthday selection effects virtually disappearing in the 1950s and 1960s, they reappeared after the emergence of labor induction and planned cesarean birth. For example, there are many fewer modern births than would be expected on Christmas Day. In addition, modern parents appear to use birth medicalization to avoid undesirable birthdays (Friday the 13th). We argue that basking in reflect glory, ethnic identity processes, and superstitions such as magical thinking all play a role in birthday selection effects. Discussion focuses on the power of social identity in day-to-day judgment and decision-making.